Efferocytosis in the Central Nervous System - Zhao, Jiayi; Zhang, Weiqi; Wu, Tingting; Wang, Hongyi; Mao, Jialiang; Liu, Jian; Zhou, Ziheng; Lin, Xianfeng; Yan, Huige; Wang, Qingqing (Frontiers in Cell and Developmental Biology, 2021)
The effective clearance of apoptotic cells is essential for maintaining central nervous system (CNS) homeostasis and restoring homeostasis after injury. In most cases of physiological apoptotic cell death, efferocytosis prevents inflammation and other pathological conditions. When apoptotic cells are not effectively cleared, destruction of the integrity of the apoptotic cell membrane integrity, leakage of intracellular contents, and secondary necrosis may occur. Efferocytosis is the mechanism by which efferocytes quickly remove apoptotic cells from tissues before they undergo secondary necrosis. Cells with efferocytosis functions, mainly microglia, help to eliminate apoptotic cells from the CNS. Here, we discuss the impacts of efferocytosis on homeostasis, the mechanism of efferocytosis, the associations of efferocytosis failure and CNS diseases, and the current clinical applications of efferocytosis. We also identify efferocytosis as a novel potential target for exploring the causes and treatments of CNS diseases.